Penilaian Dimensi Sosial Kelayakan Huni Permukiman (Studi Kasus: Kampung Deret Petogogan) - Rizkita, Safynatus Mayar Bening; Rahayu, Murtanti Jani; Rini, Erma Fitria (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
Livability is an important concept in urban planning that encompasses various aspects, such as housing quality, access to infrastructure, and social and environmental comfort. In Indonesia, the issue of adequate housing remains a challenge, especially in major cities like DKI Jakarta, which faces rapid population growth and limited land availability. To address this issue, the government has implemented various settlement revitalization programs, one of which is the Kampung Deret Program, aimed at improving the quality of slum settlements through infrastructure upgrades and housing improvements. Kampung Deret Petogogan is one of the locations where this program has been implemented and has undergone various physical and social changes since its implementation. Although the program has had a positive physical impact, evaluations of livability often remain limited to objective indicators, such as building conditions and the availability of facilities. However, subjective indicators such as sense of community, sense of safety, and participation also play a crucial role in determining the quality of life in a settlement. Therefore, this study aims to examine the livability of Kampung Deret Petogogan more holistically by considering subjective indicators. Through this approach, it is expected to provide a more comprehensive understanding of the program's effectiveness and the factors influencing the livability quality of the settlement area.